DEVELOPMENT OF INFORMATION SUPPORT FOR FISCAL RISK MANAGEMENT WITHIN CRISES - Yana Oliinyk; Maria Kucheriava; Liliia Korytnyk; Tetiana Dmytrenko; Olga Kuzminska; Konstantin Lagunov (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
Crisis phenomena, such as economic downturns, health emergencies and geopolitical conflicts, had a significant impact on the transparency of information support for public financial management processes and the development of digitalization of the economy. The objective of the study is to assess the current state of information support and transparency of the management of fiscal risks caused by state-owned enterprises' activities under uncertainty. Within the study, the existing international approaches to identifying and assessing fiscal risks are analyzed; the areas for improving information support for managing fiscal risks caused by the activities of state-owned enterprises in emergency situations are identified; the impact of digital finance development on mitigating fiscal risks caused by emergencies is assessed. Proposals to increase the transparency of public finances and create additional revenues to the state budget by the development of innovative technologies are substantiated. Implementation of fiscal and monetary policy measures to mitigate the impact of COVID-19 and ensure sustainable post-pandemic recovery requires relevant financial information reflecting the country's financial position. A reliable source of such information is public financial and budgetary statements prepared by IPSAS and on an accrual basis. Given the negative impact of uncertainty caused by the coronavirus pandemic and war on the activities of state-owned enterprises, an important tool for improving the efficiency of fiscal risk management is the unification of approaches to establishing indicators for assessing relevant risks and providing information for their calculation. In response to lockdowns and social distancing measures during crises, citizens have increasingly relied on digital channels to access government services, pay taxes, and receive financial support. This has necessitated improved digital infrastructure and service delivery mechanisms.